Relationship between quality of care and length of stay in the emergency department: A systematic literature review - Sunardi Sunardi; Pingka Ayulia Pradiarti (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Quality of care affects patient outcomes and health system efficiency. In the emergency department, length of stay is an important indicator influenced by several factors such as clinical skills, communication, and resource management. Purpose: To explore the relationship between quality of care and length of stay in the emergency department. Method: A Systematic Literature Review (SLR) with PRISMA guidelines, reviewing articles between 2014 and 2024 regarding the impact of quality of care on length of stay in the emergency department. Results: Decreased quality of care, such as delays in service and lack of resources, can increase length of stay, while better care can reduce length of stay. Conclusion: Improving the quality of care in the emergency department can reduce length of stay and result in better and more efficient care. Further research is needed to identify specific strategies to improve quality and reduce length of stay.